Designing Manhole in Water Transmission Lines Using Flow3D Numerical Model - Azin Movahedi; Ali Delavari; Massoud Farahi (Salehan Institute of Higher Education, 2015)
Using cascades and drops existing in flow path has a history of 3000 years. Particularly, Roman engineers employed stepped spillways with the same idea in several countries; however, there are few information about the hydraulic performance of aqueducts. Most of these channels have flat long cross sections with low torsions (variable slope) such that they can encompass cascade and steep spillways or dopshaft. Given that there are few studies conducted on dropshafts, the present paper attempted to discuss about such structures in flow path and water transmission lines as well as introducing the existing principles and relations and present, the obtained results of designing though Flow3D. The obtained error percentage was about 20% which is acceptable for numerical studies.